Discursos sobre corpo, gênero e sexualidade na educação do Colégio de Aplicação da Universidade Federal de Sergipe - Oliveira, Anselmo Lima de (2016)
The school has a lot more than buildings, equipment, books, library, contents, people. There people learn a lot more than Biology, Math, Portuguese, practice sports like swimming, soccer, Brazilian street fight. People learn to be people. People who respect, who do not humiliate, who hug and kiss. These people have body and a body that speaks. These bodies have sexualities and are gendered. The purpose of this research is to analyze the speeches on the themes gender, body and sexuality at Aplicação School of the Federal University of Sergipe (CODAP / UFS). The main guiding question of this research is to understand the speeches go through the themes of gender, body and sexuality in CODAP/UFS. As theoretical contributions, poststructuralist references were used, such as Michel Foucault, Guacira Lopes Louro, David Le Breton, Judith Butler and Marlucy Alves Paraiso. The theoretical and methodological approach to the development of this study was based on the qualitative approach, having interviews as data collection technique in CODAP / UFS, with thirteen participants, seven teachers and five high school students, as well as a psychologist. For data analysis was used the speech analysis method in Foucault's perspective. The analysis of the demonstrated data shows that biological, religious, educational, scientific, moralistic discourses can be found throughout out the speeches of the participants on the themes of gender, body and sexuality, producing representations that both undergo or subvert heteronormativity presente at the school.